Influence of visual feedback persistence on visuo-motor skill improvement - Unell, Alyssa; Eisenstat, Zachary M.; Braun, Ainsley; Gandhi, Abhinav; Gilad-Gutnick, Sharon; Ben-Ami, Shlomit; Sinha, Pawan (Scientific reports, 2021)
Towards the larger goal of understanding factors relevant for improving visuo-motor control, we investigated the role of visual feedback for modulating the effectiveness of a simple hand-eye training protocol. The regimen comprised a series of curve tracing tasks undertaken over a period of one week by neurologically healthy individuals with their non-dominant hands. Our three subject groups differed in the training they experienced: those who received ‘Persistent’ visual-feedback by seeing their hand and trace evolve in real-time superimposed upon the reference patterns, those who received ‘Non-Persistent’ visual-feedback seeing their hand movement but not the emerging trace, and a ‘Control’ group that underwent no training. Improvements in performance were evaluated along two dimensions—accuracy and steadiness, to assess visuo-motor and motor skills, respectively. We found that persistent feedback leads to a significantly greater improvement in accuracy than non-persistent feedback. Steadiness, on the other hand, benefits from training irrespective of the persistence of feedback. Our results not only demonstrate the feasibility of rapid visuo-motor learning in adulthood, but more specifically, the influence of visual veridicality and a critical role for dynamically emergent visual information.